Evolution of Matrix Gla and Bone Gla Protein Genes in Jawed Vertebrates - Leurs, Nicolas; Martinand-Mari, Camille; Ventéo, Stéphanie; Haitina, Tatjana; Debiais-Thibaud, Mélanie (Frontiers in Genetics, 2021)
Matrix Gla protein (Mgp) and Bone Gla protein (Bgp) are vitamin-K dependent proteins that bind calcium in their γ-carboxylated versions, in mammals. They are recognized as positive (Bgp) or negative (Mgp and Bgp) regulators of biomineralization in a number of tissues, including skeletal tissues of bony vertebrates. The Mgp/Bgp gene family is poorly known in cartilaginous fishes, which precludes the understanding of the evolution of the biomineralization toolkit at the emergence of jawed vertebrates. Here we took advantage of recently released genomic and transcriptomic data incartilaginous fishes and described the genomic loci and gene expression patterns of the Mgp/Bgp gene family. We identified three genes Mgp1, Mgp2 and Bgp, in cartilaginous fishes instead of the single previously reported Mgp gene. We describe their genomic loci, resulting in a dynamic evolutionary scenario for this gene family including several events of local (tandem) duplications, but also of translocation events, along jawed vertebrate evolution. We describe the expression patterns of Mgp1, Mgp2 and Bgp in embryonic stages covering organogenesis in the small-spotted catshark Scyliorhinus canicula and present a comparative analysis with Mgp/Bgp family members previously described in bony vertebrates, highlighting ancestral features such as early embryonic, soft tissues and neuronal expressions, but also derived features of cartilaginous fishes such as expression in fin supporting fibers. Our results support an ancestral function of Mgp in skeletal mineralization, and a later derived function of Bgp in skeletal development that may be related to the divergence of bony vertebrates.